Transmedia games “I love to read”: immersive experiences, affinity spaces, connected learning and bond creation with the community - Lugo Rodríguez, Nohemí (2021)
This article explores the experiences and learning of university students when participating in different roles (players, actors, and staff) in transmedia games. A case study was carried out at the university that analyzes 9 of the 11 “I love to read” games carried out from 2014 to 2019 to promote reading. The participation in theseevents has been approximately 1048 university students. The results and findings indicate that these games are immersive experiences that generate readiness and diverse learning, arouse interest and benefit the university community. I conclude that they generate a space of intramural affinity and are an effective strategy to promote connected learning.